ANALISIS FAKTOR PENYEBAB KEMATIAN IBU DI KABUPATEN CILACAP TAHUN 2016 - ., Johariyah (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2017)
Every minute a mother died because of the cause related to pregnancy and childbirth. From each death, it is estimated that there are 100 women who survived delivery time, but experienced physical disability and pain due to pregnancy and childbirth. The results showed, if a baby is less than 3 months of age to die of his mother, then the probability of survival of the baby is only about 30%. This means that if a mother died when her baby was less than 3 months then the risk of death by 70%. The research in this study is a case of control with a retrospective approach, namely data retrieval starting from the outcome. In this study we compared the possible factors causing maternal deaths among mothers who died with mothers who did not die of pregnancy, childbirth or childbirth. Data analysis in this research is done by using SPSS program. Data analysis is done in two stages. The first step is to conduct descriptive analysis of Age variable, education level, Parity, Number of Visits of Antenatal Care, Birth Attenden based on Maternal Death. In addition to the description of maternal deaths based on causes, time of death, place of incidence and duration of care in hospitals. The second stage analyzes the relationship between Age, education level, Parity, Number of Antenatal Care Visits,, Birth helpers using Chi-Square. The results showed that most of the incidence of maternal mortality in Kabupaten Cilacap occurred at low risk age (60%), in terms of education with low education status (80%), in terms of parity in low risk category (70%), the number of visits of ANC at the frequency of 4X (100%), in the case of birth attendant is entirely assisted by health personnel (100%), based on the most causes in other causes category (52%), 64%), in terms of place of death in the hospital (92%), and in terms of duration in the hospital within <48 hours (56.6%). Chi Square analysis results obtained that the level of education and Parity have a significant relationship to maternal mortality (p <0.05). As for age variable, ANC frequency, birth attendant did not significantly influence maternal mortality (p> 0,05). Keywords: Maternal Mortality factor